Managing Helicobacter pylori infection: transitioning from conventional to alternative treatment approaches - Öcal, Serhat (The European Research Journal, 2024)
Helicobacter pylori, an essential constituent of the gastric microbiome in those infected, is commonly associated with medical conditions such as chronic gastritis, peptic ulcer disease, and gastric cancer. In recent years, the growing resistance to antibiotics worldwide has emerged as a substantial hurdle in the effective treatment of H. pylori infection. Consequently, it has necessitated the exploration of innovative treatment strategies aimed at bolstering the potency of existing antibiotic-based eradication therapies. Such avant-garde strategies include the incorporation of probiotics and prebiotics as complementary measures to H. pylori treatment, the use of antimicrobial peptides as potential replacements for traditional antibiotics, and the application of photodynamic therapy via ingestible devices. Other advanced methodologies entail deploying drug delivery systems that utilize microparticles and nanoparticles, the invention of vaccines, the exploration of natural products, and the potential use of phage therapy. This review offers a contemporary synopsis of these burgeoning strategies designed to suppress H. pylori, delving into their strengths, hurdles, and aspects to consider during their development. A significant achievement would be the creation of an efficient human vaccine; however, previous attempts at developing such vaccines have met with obstacles or even cessation. Numerous natural products have displayed anti-H. pylori properties, predominantly in laboratory environments. Nonetheless, a requirement remains for more extensive clinical studies to fully comprehend their role in exterminating H. pylori. Finally, phage therapy, while demonstrating potential as a suitable alternative, grapples with considerable challenges, chiefly the isolation of highly virulent bacteriophages that specifically target H. pylori.